The Transposition of the CSR Directive into German Commercial Law - Uwer, Dirk; Schramm, Michael (P.A. Persona e Amministrazione, 2018)
Through the “Act to Strengthen the Non-financial Reporting by Corporations in their Management and Group Management Reports” (Gesetz zur Stärkung der nichtfinanziellen Berichterstattung der Unternehmen in ihren Lage- und Konzernlageberichten) (CSR Directive Transposition Act, „CSR-RUG“) of 11 April 2017[1], the German Bundestag implemented Directive 2014/95/EU (“CSR Directive”)[2] into German law. Following the European impetus, the CSR-RUG enriches the traditional repertoire of forms of action under environmental law by a further instrument. Already the regulatory context gives an idea of its atypical nature: The centrepiece of the CSR-RUG is the amendment of and addition to the Third Book of the German Commercial Code (Handelsgesetzbuch, “HGB”), which deals with the “trading books” of undertakings, i.e., accounting and reporting requirements. Since the reporting year 2017, large capital market-oriented corporations must report extensively within the framework of their annual management reports on their activities and effects in certain areas of “Corporate Social Responsibility”. This also includes environmental matters. The transparency and publicity this entails is intended to generate positive stimuli for more responsible, sustained and not least of all environmentally friendly entrepreneurial action. Following a brief presentation of the European legal bases and their implementation in Germany (I.), we will classify the provisions within the underlying concept of Corporate Social Responsibility (II.) and analyse and systemise the governance effects of non-financial reporting (III.). A few remarks on selected aspects of the chosen approach and its implementation (IV.) as well as an outlook summarising our conclusions (V.) will complete this article. By detailing the German approach to transposing the CSR Directive, this paper intends to provide an example of the challenges member state legislators face when complying with modern governance concepts such as Corporate Social Responsibility by way of non-financial reporting obligations. [1] Federal Law Gazette, Part I 2017, 802 et seq. [2] Directive 2014/95/EU of the European Parliament and of the Council 22 October 2014 amending Directive 2013/34/EU as regards disclosure of non-financial and diversity information by certain large undertakings and groups, OJ EU No. L 330, p. 1.